2017
DOI: 10.3126/jkmc.v5i1.18263
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with retinopathy of prematurity among neonates in a tertiary care hospital in Nepal

Abstract: Background: Retinopathy of prematurity is a vascular retinal disease that can cause blindness in premature new born babies. Several risk factors are associated with the incidence of ROP. Information and data on risk factors associated with ROP in context to Nepalese population is scarcely documented in literature. Objectives: The purpose of this study was to evaluate the risk factors of retinopathy of prematurity in premature infants admitted in the neonatal intensive care unit of Tribhuvan University Teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…This result agrees with studies done in Jordan and Japan which showed that the female has about six times more likely to develop DPN compared with male [ 37 , 38 ]. However, The results of the study are in stark contrast to those of most studies in the literature [ 39 , 40 ] whereas another study found no significant association and variation in gender [ 41 ]. This discrepancy may be a result of differences in the tests used to measure neuropathic changes, the duration of diabetes, and the level of glycemic control for the subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…This result agrees with studies done in Jordan and Japan which showed that the female has about six times more likely to develop DPN compared with male [ 37 , 38 ]. However, The results of the study are in stark contrast to those of most studies in the literature [ 39 , 40 ] whereas another study found no significant association and variation in gender [ 41 ]. This discrepancy may be a result of differences in the tests used to measure neuropathic changes, the duration of diabetes, and the level of glycemic control for the subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Smoking was more common among subjects with DPN compared to those without the illness. It was at this stage that the probability level was 0.004 [19][20][21] . In their investigation on the prevalence of DPN in a cohort of diabetic volunteers, Dipika Bansal et al could not find a statistically significant difference in smoking prevalence between individuals with and without DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy of prematurity (ROP), previously called retrolental fibroplasias, is a vasoproliferative disorder of the retina which occurs principally in premature children due to defective vasculogenesis 1 .In full-term infants, the retina and its vessels are fully developed; hence, ROP can only affect preterm infants. 2 The incidence of retinopathy of prematurity in Nepal was 22.6% 3 and 25.45% (n=14). 4 Pediatricians working in the NICU are the first physicians to examine preterm infants, thus assessing their knowledge regarding ROP is crucial.…”
Section: Introductionmentioning
confidence: 98%